Imperfect Information, Lagged Labor Adjustment and the Great Moderation - Tim Willems; Sweder van Wijnbergen (Tinbergen Institute, 2009)
This paper first documents the increase in the time lag with which labor input reacts to output fluctuations (the labor adjustment lag) that is visible in US data since the mid-1980s. We show that a lagged labor adjustment response is optimal in a setting where there is uncertainty about the persistence of shocks and where labor input is costly to adjust. We then present evidence that both the nature of shocks as well as labor adjustment costs may have changed during the 1980s in a direction that could explain the observed increase in the lag. Finally, we argue that the increased labor adjustment lag has the potential to explain some macroeconomic puzzles that characterize post-1984 US data, such as the reduced procyclicality of labor productivity and the reduction in output volatility (known as the Great Moderation).
Keywords: E24; E32; J23; J24; 330; imperfect information; labor adjustment; jobless growth; option value of waiting; Great Moderation; Unvollkommene Information; Konjunktur; Beschäftigungseffekt; Arbeitslosigkeit; Wirtschaftliche Anpassung; USA